Penyelesaian Perkara Perkawinan Campuran Melalui Hukum Perdata Internasional - Logo Igo Karmed; Karina Alifia Maharani; Moh Imam Mahmudin; Restu Teguh Imani; Tsabisa Zaskia Putri Maharani (Jurnal Relasi Publik, 2023)
This research is conducted with the aim of analyzing the impact of mixed marriages between Indonesian citizens and foreign nationals according to the provisions of regulations No. 1 of 1974 concerning Marriage and No. 12 of 2006 concerning the Citizenship of the Republic of Indonesia, from the perspective of International Private Law (IPL). Employing normative research methods, this study utilizes legal materials in its examination. The collection of materials involves literature studies.Based on the research, in marriages involving individuals with different citizenships, the applicable laws for them also differ. The Marriage Law does not explicitly regulate the legal consequences arising from mixed marriages. The provisions governing its legal consequences state that the status of children from mixed marriages is regulated according to the acquired citizenship, determining the applicable law.Through the above regulations, certainty is still provided in the protection for women marrying foreign nationals and the children resulting from mixed marriages.